Thinking Together Digitalization and Social Innovation in Rural Areas: An Exploration of Rural Digitalization Projects in Germany - Ariane Sept (European Countryside, 2020)
Digitalization and social innovation are often discussed separately and without any spatial reference or in relation to cities, although newer works show the importance of social innovation also for rural areas. Existing digitalization projects illustrate the potential of digital technologies for rural development. Current debates on smart villages refer to both digitalization and social innovation but still in a rather unsystematic way. The paper seeks to think together digitalization and social innovation in rural areas more systemically and proposes to conceptually connect them with the help of sensitizing concepts, which are developed out of debates on social and digital social innovation. Along these concepts, the paper explores rural digitalization projects in Germany. On the one hand, this highlights the spectrum of these initiatives and, on the other hand, provides a framework under which digitalization and social innovation can be analyzed and smart villages may be supported systematically.
Keywords: 320; smart villages; digital social innovation; rural development